2017
DOI: 10.1007/s10067-017-3858-4
|View full text |Cite
|
Sign up to set email alerts
|

Low level of circulating basophil counts in biopsy-proven active lupus nephritis

Abstract: Basophils have been shown to be important players in promoting lupus nephritis (LN). However, the relationship between circulating basophil counts and renal pathology activity of LN remains unclear. In this retrospective study, 159 clinical and pathology samples from patients with biopsy-proven LN were analyzed. The renal activity and classification were evaluated according to renal pathology. The correlations between circulating basophil counts and renal pathology activity index were assessed. Overall, circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Very recently, Pellefigues et al suggested that antagonizing PTGDR-1 and -2 (prostaglandin D2 receptors), by using laropiprant and ramatroban (two FDA-approved drugs for the treatment of some forms of dyslipidemia and allergic rhinitis, respectively) in human lupus, might be a quick and accessible therapeutic resource [ 48 ]. Indeed, they found that the expression of those receptors was increased on basophils from patients with SLE, and the interaction of PGD2–PTGDRs was associated with basophil activation and tissue extravasation during active lupus, which may actually be consistent with previous observations by Liang et al, despite their methodological limitations [ 45 , 47 , 48 ]. However, under the therapeutic point of view, in terms of potential implication of basophils and/or IgE production in the pathophysiological process of SLE, the most interesting clinical application is the recent trial of omalizumab (anti-IgE monoclonal antibody) in patients with SLE.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Very recently, Pellefigues et al suggested that antagonizing PTGDR-1 and -2 (prostaglandin D2 receptors), by using laropiprant and ramatroban (two FDA-approved drugs for the treatment of some forms of dyslipidemia and allergic rhinitis, respectively) in human lupus, might be a quick and accessible therapeutic resource [ 48 ]. Indeed, they found that the expression of those receptors was increased on basophils from patients with SLE, and the interaction of PGD2–PTGDRs was associated with basophil activation and tissue extravasation during active lupus, which may actually be consistent with previous observations by Liang et al, despite their methodological limitations [ 45 , 47 , 48 ]. However, under the therapeutic point of view, in terms of potential implication of basophils and/or IgE production in the pathophysiological process of SLE, the most interesting clinical application is the recent trial of omalizumab (anti-IgE monoclonal antibody) in patients with SLE.…”
Section: Discussionsupporting
confidence: 81%
“…In a more recent study, the same authors showed that circulating basophil counts were frequently lower in patients with active lupus nephritis and negatively correlated with disease activity. However, basophils were counted with an automatic blood cell analyzer, which is not the best method to precisely assess such a rare blood cell population [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study indicated that basophils contribute to LN development by promoting autoantibody production and that LN-like disease was suppressed when basophils were depleted in a mouse model [ 33 ]. A previous study of patients with biopsy-proven LN showed that basophil counts were decreased in patients with nephritis compared with those in patients without nephritis and that basophil counts were negatively correlated with pathological activity [ 34 ]. Based on previous and the current results, basophil counts or proportions may be a biomarker of LN.…”
Section: Discussionmentioning
confidence: 99%
“…Basophils are recruited into skin lesions of SLE patients, where they are implicated in promoting tissue damage (71). Data from a retrospective clinical study suggest that blood basophils could be potentially used as a biomarkers of disease activity in SLE (72, 73). By using the Lyn −/− mice, that develop a lupus-like disease late in life, Charles et al showed that basophils are key players in promoting inflammation and supporting ANA production by B cells (69).…”
Section: Innate Immunity In Slementioning
confidence: 99%